Species diversity of Amorphophallus (Araceae) in Bali and Lombok with attention to genetic study in A. paeoniifolius (Dennst.) Nicolson - AGUNG KURNIAWAN; I PUTU AGUS HENDRA WIBAWA; BAYU ADJIE` (Biodiversitas Journal of Biological Diversity, 2011)
Kurniawan A, Wibawa IPAH, Adjie B (2011). Species diversity of Amorphophallus (Araceae) in Bali and Lombok with attention to genetic study in A. paeoniifolius (Dennst.) Nicolson. Biodiversitas 12: 7-11. Amorphophallus belongs to Araceae family that consists of more than 170 species worldwide and distributed predominantly in tropical countries, especially in Asia and Africa. The study of Amorphophallus in Bali and Lombok Islands had been conducted to reveal its diversity. Genetic study was also conducted among Amorphophallus paeoniifolius species to recognize the variation within the species. The fieldworks showed three species Amorphophallus distributed in Bali, notably A. muelleri Blume, A. paeoniifolius (Dennst.) Nicolson, A. variabilis Blume and two species in Lombok, notably A. muelleri and A. paeoniifolius. Var. hortensis and var. sylvestris were two varieties of A. paeoniifolius that commonly found either in Bali or in Lombok. Genetic study on A. paeoniifolius indicated that there was no genetic variation in cpDNA region of trnL-F IGS within the species.